Environmental Influences on Children's Physical Activity: Quantitative Estimates Using a Twin Design - Fisher, Abigail (Public Library of Science, 2010)
BACKGROUND: Twin studies offer a ‘natural experiment’ that can estimate the magnitude of environmental and genetic effects on a target phenotype. We hypothesised that fidgetiness and enjoyment of activity would be heritable but that objectively-measured daily activity would show a strong shared environmental effect. METHODOLOGY/PRINCIPAL FINDINGS: In a sample of 9–12 year-old same-sex twin pairs (234 individuals; 57 MZ, 60 DZ pairs) we assessed three dimensions of physical activity: i) objectively-measured physical activity using accelerometry, ii) ‘fidgetiness’ using a standard psychometric scale, and iii) enjoyment of physical activity from both parent ratings and children's self-reports. Shared environment effects explained the majority (73%) of the variance in objectively-measured total physical activity (95% confidence intervals (CI): 0.63–0.81) with a smaller unshared environmental effect (27%; CI: 0.19–0.37) and no significant genetic effect. In contrast, fidgetiness was primarily under genetic control, with additive genetic effects explaining 75% (CI: 62–84%) of the variance, as was parent's report of children's enjoyment of low 74% (CI: 61–82%), medium 80% (CI: 71–86%), and high impact activity (85%; CI: 78–90%), and children's expressed activity preferences (60%, CI: 42–72%). CONCLUSIONS: Consistent with our hypothesis, the shared environment was the dominant influence on children's day-to-day activity levels. This finding gives a strong impetus to research into the specific environmental characteristics influencing children's activity, and supports the value of interventions focused on home or school environments.